انعكاس سياسات التنمية الريفية على الأمن الغذائي في الجزائر - بلقلة, براهيم; صلاح, محمد; مطاي, عبد القادر (Université de M'sila, 2017)
The aim of this research is to review the most important policies and programs initiated by Algeria in the period 2000-2013forthe sake of develop the rural and community gricultural sector in order to achieve food security. The rural community is the oundation stone for the development of the agricultural sector and the provision of food needs. At the end, we have noticed that Algeria has made much efforts to achieve food security through the establishment of development policy ambitious and sustainable, manifested sets in a broad package of plans and programs leading to a marked improvement on the level of the agricultural sector and the rural community since the beginning of the third millennium, and yet, in spite of those accomplishments, however, there are a umber of shortcomings and challenges and that the decision-makers must be faced to promote the agricultural sector and the development of the rural community to trengthen the country's food security.
Keywords: rural community, agricultural sector, food security.